ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGANGGURAN PEREMPUAN - Ida Ayu Nyoman Saskara; David Kaluge (Journal of Indonesian Applied Economics, 2009)
The aim of this is to analyses women unemployment based on Indonesia Provinceusing  inflation,  investment,  women  involvement  at  labor market,    and  also meninvolvement at labor market as independent varaibles.The panel data is used from26 provinces in Indonesia for 5 years (2002-2006), using double log regression. Theresult  shows  that  employing women  have  negative    effect  and  significant, whileemploying men has positive effect and significant to the women employment. Inflationand investment have positive and negative effect but insignificant.Keywords: inflation, investment, women unemployment and labor market